Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10334-016-0563-2
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based assessment of liver perfusion and hepatocyte injury in the murine model of acute hepatitis

Abstract: ObjectiveTo assess alterations in perfusion and liver function in the concanavalin A (ConA)-induced mouse model of acute liver failure (ALF) using two magnetic resonance imaging (MRI)-based methods: dynamic contrast-enhanced MRI (DCE-MRI) with Gd-EOB-DTPA contrast agent and arterial spin labelling (ASL).Materials and methodsBALB/c mice were studied using a 9.4 T MRI system. The IntraGateFLASHTM and FAIR-EPI pulse sequences were used for optimum mouse abdomen imaging.ResultsThe average perfusion values for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Several DCE studies of the abdominal organs in mice have been previously reported including examination of pancreas [ 41 , 42 , 43 , 44 ], placenta [ 45 , 46 ], kidney [ 24 , 47 ] and liver [ 2 , 48 , 49 , 50 , 51 ]. Most of these studies employed full Cartesian sampling for acquisition of the dynamic data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several DCE studies of the abdominal organs in mice have been previously reported including examination of pancreas [ 41 , 42 , 43 , 44 ], placenta [ 45 , 46 ], kidney [ 24 , 47 ] and liver [ 2 , 48 , 49 , 50 , 51 ]. Most of these studies employed full Cartesian sampling for acquisition of the dynamic data.…”
Section: Discussionmentioning
confidence: 99%
“…However, the resulting dynamic data are often corrupted by motion artifacts. A variety of approaches for minimization of motion artifacts have also been proposed including securing the tissue of interest with a plastic platen [ 41 ], prospective gating [ 18 ], non-affine image registration [ 42 ] and use of navigator echoes [ 49 ]. Though application of these methods generally reduces the frequency of occurance of motion artifacts, some data corruptoin persists.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, we plan to validate predictions of our model against post-operative clinical measurements. Water-fat quantification techniques using MRI are available to measure tissue perfusion with quantitative characterization of parenchymal and microcirculatory changes (66) and to study the extent of liver damage (66, 67).…”
Section: Discussionmentioning
confidence: 99%
“…ConA for the induction of ALF is well described in mice, though not well characterized in other animal models. ConA is dosed between 8–35 mg/kg IV, dissolved in sterile PBS or NS (it is unknown whether it can be administered with the same effect IP) ( Byk et al, 2016 ; Tadokoro et al, 2017 ). Dose finding experiments are recommended prior to beginning experiments, as its efficacy is known to vary by batch.…”
Section: Survey Methodologymentioning
confidence: 99%